Pemantauan Parameter Fisik dan Aktivitas Mikroorganisme Aerob di Unit Oxidation Ditch Instalasi Pengolahan Lumpur Tinja - Setia Wati, Syaharani; Rachmanto, Tuhu Agung (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Oxidation ditch is one of the widely used biological sewage treatment systems to treat fecal sludge by means of continuous aeration. This system relies on the activity of aerobic microorganisms, which require dissolved oxygen to break down organic compounds in wastewater effectively and sustainably. This study aims to monitor three important parameters in the oxidation ditch unit at the Instalasi Pengolahan Lumpur Tinja (IPLT), namely Dissolved Oxygen (DO), temperature, and Sludge Volume 30 minutes (SV30). DO and temperature measurements are carried out routinely to ensure that environmental conditions continue to support the biological process in the aeration channel optimally. Meanwhile, the SV30 value is used to evaluate the effectiveness of activated sludge precipitation formed during the treatment process. Observations show that fluctuations in DO and temperature affect the performance of the treatment system, while the SV30 value reflects the sludge quality and overall process stability. Monitoring these three parameters is important to maintain the efficiency, reliability and sustainability of the overall domestic effluent treatment process.